Astrocytic ET‐1 System Determines Microglia Phenotype Following Spinal Cord Injury - Bingqiang He; Si Xu; Mengdi Li; Hui Li; Shaolan Li; Li Niu; Honghua Song; Rixin Cai; Yue Zhou; Zhilong Cao; Yingjie Wang; Yongjun Wang (Advanced Science)
Abstract Microglia/macrophages accumulate at the lesion site by switching toward pro‐inflammatory (M1)‐dominant phenotype at the acute phase following spinal cord injury (SCI). Such biased polarization shapes the functional outcomes by expanding tissue damage. In the present study, the astrocytic endothelin‐1 (ET‐1) system is revealed to be immediately activated after SCI, driving microglia polarization toward M1, but suppressing toward M2 phenotype through activation of transcription coactivator YAP via ETA and ETB receptors. In addition, the activation of astrocytic ET‐1 system results in elevation of blood plasma ET‐1 level, suggesting a high diagnostic value. SCI‐induced thrombin is pinpointed as a crucial activator of the astrocytic ET‐1 system. The serine protease dramatically promotes the astrocytic expression of preproendothelin‐1 (ppET‐1) through protease‐activated receptor‐1 (PAR‐1)/RhoA/NF‐κB and PAR‐1/MAPKs/NF‐κB signal pathways. Meanwhile, it induces the expression of astrocytic endothelin‐converting enzyme 1 (ECE‐1) responsible for mature ET‐1 processing. Pharmacological inhibitors of PAR‐1 and ET‐1 are shown to be highly efficient in microglia M1 phenotype reversion and favorable for the recovery of rat locomotor function after SCI. The findings have revealed a novel mechanism of M1 microglia/macrophages swarming at lesion sites at the acute phase following SCI, and provide potential therapeutic approaches for neuroinflammation by targeting the astrocytic ET‐1 system.